PERBANDINGAN RESISTENSI FRIKSIONAL ANTARA LIGASI BRAKET PREADJUSTED ROTH KONVENSIONAL DAN SELF LIGATING PADA EMPAT TINGKAT KEPARAHAN MALPOSISI GIGI MENGGUNAKAN KAWAT BUSUR Ni-Ti - , Nur Rachmawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Preadjusted self ligating bracket is claimed having less friction due to the tube-like shape, accommodating the wire slide easily, but rigid clip of this bracket limiting the working span. The use of wire ligature tightened onto the slot of conventional bracket and unwound 3 times resulted less friction. The aim of this study were to know the frictional resistance differences between preadjusted Roth conventional and self ligating bracket using Ni-Ti archwire, the difference due to increasing of tooth malposition as well as the interaction between the bracket types and tooth malposition. Eighty preadjusted Roth metal bracket (40 conventional, and 40 self ligating), 16 buccal tube were bonded on acrylic typodont of lower arch after set 4 degree of malposition due to Little (none, mild, moderate, and severe). The archwires were placed, ligated, and wetted using artificial saliva (pH 7). The frictional resistance was tested using universal testing machine. The data were collected and analyzed using two way of variance analysis. No differences were showed on the frictional resistance between preadjusted Roth conventional and self ligating bracket, as well as the interaction between the bracket types and tooth malposition (p>0,05). Frictional resistance due to increasing of tooth malposition were different (p<0,05). The conclusion: the frictional resistance between preadjusted Roth conventional and self ligating bracket were same, the frictional resistance increased with the increasing of tooth malposition, but there were no interaction between bracket types and tooth malposition.